Wales, the West Country, and the Midlands in female-authored novels, 1810-1820 - Hawley-Sibbett, Ruby Ellen (2023)
This thesis focuses on the use of regional spaces in a corpus of forty-four female-authored novels set in Wales, the West Country, and the Midlands, published between 1810 and 1820. By so doing, it aims to address a gap in current scholarship on Romantic regionalism. It argues that these case study regions form a coherent grouping within the wider phenomenon of the English and Welsh regional novel, due to their contiguity, their many similarities, and their shared differences from other spaces. This study focuses on the 1810s as a significant point in the development of the regional novel genre. It considers trends which correlate with formal regional boundaries, as well as transregional themes, particularly remoteness and retirement.